2016
DOI: 10.1097/md.0000000000003325
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MicroRNAS in Ankylosing Spondylitis

Abstract: Ankylosing spondylitis (AS) is a common and genetically heterozygous inflammatory rheumatic disease characterized by new bone formation, ankylosis and inflammation of hip, sacroiliac joints and spine. Until now, there is no method for early diagnosis of AS and the effective treatment available for AS patients remain largely undefined.We searched articles indexed in PubMed (MEDLINE) database using Medical Subject Heading (MeSH) or Title/Abstract words (“microRNA” and “ankylosing spondylitis”) from inception up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Indeed, there are currently no straightforward predictors of a good response to anti-TNF-α drugs and significant percentage of patients fail to respond to treatment (25–38% of etanercept patients, 21–42% of infliximab patients) (Seymour et al 2001 ). Recent studies have shown that miRNA play an important role in RA and AS diagnosis and dysregulated miRNA expression seems to contribute to the molecular mechanisms of the disease (Chen et al 2015 ; Li et al 2016 ; Prajzlerova et al 2017 ). MiRNAs are short (approximately 21 nucleotides long) non-coding RNAs that can influence mRNA processing at the post-transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are currently no straightforward predictors of a good response to anti-TNF-α drugs and significant percentage of patients fail to respond to treatment (25–38% of etanercept patients, 21–42% of infliximab patients) (Seymour et al 2001 ). Recent studies have shown that miRNA play an important role in RA and AS diagnosis and dysregulated miRNA expression seems to contribute to the molecular mechanisms of the disease (Chen et al 2015 ; Li et al 2016 ; Prajzlerova et al 2017 ). MiRNAs are short (approximately 21 nucleotides long) non-coding RNAs that can influence mRNA processing at the post-transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of AS blood and serum have implicated miRs in AS 9. However, the miR profile of AS Th17 cells has not been studied previously.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has shown that aberrant miRNA expression is linked to the regulation of autophagy [16]. Studies have shown that miR-150, miR-342-5p, miR-16, miR-221, miR-99b, let-7b, let-7i, and miR-513-5p were higher and that miR-218, miR-30e, miR-199a-5p, miR-409-3p, and miR-215 were lower in the T cells of AS than in healthy counterparts [17]. MiR-199a-5p, a recently discovered miR, has been reported to be dynamically regulated in the T cells of AS patients, suggesting that miR-199a-5p may play a role in the development of AS.…”
Section: Introductionmentioning
confidence: 99%